Comparison of phenotypic properties of innate lymphoid cells at various stages of rheumatoid arthritis - O. S. Boeva; V. A. Kozlov; A. E. Sizikov; M. A. Korolev; O. A. Chumasova; V. O. Omelchenko; Yu. D. Kurochkina; E. A. Pashkina (Медицинская иммунология, 2023)
Autoimmune diseases currently take a leading place in terms of frequency of occurrence in the population, among which 1 percent is occupied by rheumatoid arthritis (RA). Remission in this type of disease is extremely rare and requires constant use of pharmacotherapy. Studying the pathogenesis of RA is necessary to study to search for new drug targets. It is known that T helpers 1 (Th) and Th17 are involved in the development of RA. However, some researchers suggest that ILCs play a role in the development of RA. ILCs are “innate analogues” of Th, due to the fact that this subpopulation synthesizes the same cytokines. ILC1 is innate analogs of Th1, ILC2-Th2, ILC3-Th17. ILCs are tissue-resident innate lymphoid cells that have functional diversity and regulate the direction of the immune response through the production of cytokines.We used peripheral blood mononuclear cells (PBMCs) from patients (n = 19) and conditionally healthy donors (n = 10) as material. The group of patients was divided biologic disease-modifying anti-rheumatic drugs (bDMARDs) and Metotrexate (MTX) and of stage of RA (early and very early arthritis, advanced and late). PBMCs were stained with monoclonal antibodies. ILCs were identified as Lin-CD127+, CD294+ILCs (ILC2) were measured in the general population, CD117-CD294-ILCs were identified as ILC1, and CD117+CD294-ILCs were identified as ILC3.We obtained the following results: ILC1 was significantly reduced in patients treated with MTX comparison with patients on bDMARDs and healthy donors. However, patients on MTX with advanced RA had low levels of ILC2 and ILC3 compared to patients on bDMARDs. ILC2 significantly increased in patients with early stages of RA comparison with patients with advanced RA. However, ILC1 was significantly reduced in patients treated with MTX, and ILC3 increased significantly in patients treated with MTX comparison with bDMARDs. Expression of PD1 on ILC1 was increased compared to patients treated with bDMARDs. However, ILC3 patients with advanced stages on MTX had increased expression of PD1 comparison with patients taking bDMARDs. The ILC3 of donors was significantly increased comparison with patients on bDMARDs.